Evolution of the Video Game Market - Wildan Ali (Journal of Games, Game Art, and Gamification, 2016)
The videogame industry had evolved since its initial appearance, and along with it, so has target market. This study attempts to analyse the trends throughout the years through observation of marketing materials such as printed and video advertisement commercials. The analysis is done by applying standard practice values employed in advertising communication on chosen samples of said commercial ads from each era of video game history.